2005
DOI: 10.1002/bem.20148
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the strength of power frequency fields against membrane electrical noise

Abstract: The possible physiological effect of power frequency fields (60 Hz in the US, 50 Hz in most other countries) is still a hotly debated issue. These relatively slow fields distribute themselves across cell membranes and a common approach has been to compare the strength of these fields to the strength of the electric noise that the membrane generates itself through Brownian motion. However, there has been disagreement among researchers on how to evaluate the membrane electric noise. In the first part of this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Avogadro constant N A = 6 × 10 23 molecules/mol (9) Faraday constant F = N A × q e = 9.65 × 10 4 C/mol (10) Dielectric field constant (free space) ε 0 = 8.85 × 10 −12 C/V/m (11) Figure 3. Left: Typical tumor environment characterized by isolated tumor cells surrounded by extracellular water.…”
Section: Application Of Hyperthermiamentioning
confidence: 99%
“…Avogadro constant N A = 6 × 10 23 molecules/mol (9) Faraday constant F = N A × q e = 9.65 × 10 4 C/mol (10) Dielectric field constant (free space) ε 0 = 8.85 × 10 −12 C/V/m (11) Figure 3. Left: Typical tumor environment characterized by isolated tumor cells surrounded by extracellular water.…”
Section: Application Of Hyperthermiamentioning
confidence: 99%
“…50 or 60 Hz) may be insuffi cient to mask the effect of external applied fi elds thus allowing the small internal fi elds that result from the relatively high conductivity of human tissue to be suffi cient just across membranes. There have been both supporters (Vincze et al, 2005 ;Bier, 2005) of this observation albeit with a different interpretation of the data, and critics such as Adair (2003) , who felt the case was still a speculation and an oversimplifi cation. The importance of these arguments is that when extended to radiofrequency and microwaves, since the higher frequencies (above a few kilohertz) are not 'biologically' active, an additional mechanism becomes essential.…”
Section: Power Frequencymentioning
confidence: 83%
“…Vincze et al [2005] suggested that heating of the extracellular matrix by external fields might conceivably lead to diffusion gradients having biological significance, and Bier [2005] pointed out that the nonequilibrium nature of membrane proteins such as ion pumps may enable them to ''capture'' electromagnetic energy to perform work that is metabolically significant.…”
Section: Discussionmentioning
confidence: 99%